An interval estimator for chlorine monitoring in drinking water distribution systems under uncertain system dynamics, inputs and chlorine concentration measurement errors - Łangowski, Rafał; Brdyś, Mieczysław A. (Zielona Góra: Uniwersytet Zielonogórski)
The design of an interval observer for estimation of unmeasured state variables with application to drinking water distribution systems is described. In particular, the design process of such an observer is considered for estimation of the water quality described by the concentration of free chlorine. The interval observer is derived to produce the robust interval bounds on the estimated water quality state variables.
Keywords: observers; bounding methods; modelling dynamics; water quality